Detection of heavy metal residues in the muscle and skin of Tilapia. - Affendi, Muhamad Ridhwan; Sabri, Jasni; Abdul Wahid, Samsuri (2011)
A study of detect the presence of heavy metals, which are Lead (Pb), Copper (Cu) and Zinc (Zn) in Tilapia cought from 3 waterways in Universiti Putra Malaysia, Serdang, Selangor was conducted. Water samples from the study sites were also sampled and analysed. These locations were in the academic areas of Universiti Putra Malaysia, Serdang campus near the agricultural and housing areas. Results showed that the mean concentration of Cu, in the water was 0.04 µg/mL and Pb and Zn were 0.03 µg/mL. The concentration of the elements tested was found to be lower than the recommended limits set by FAO/WHO but the concentration of Pb almost breached the limit of 0.05 µg/mL. The mean concentration of Pb in the fish muscles (0.64 µg/g) did not exceed the permissible limits set by FAO/WHO (1.5 µg/g) and the Malaysian Food Regulation (1.0 µg/g). The concentration of Cu in the fish muscle was much lower (2.13 µg/g) than the permissible limits set by the WHO (10.0 µg/g) and the Malaysian Food Regulation (30.0 µg/g). The highest element that had accumulated in the fish muscle was Zn (8.28 µg/g). However. The concentration of Zn did not exceed the permissible limits set by FAO/WHO (150.0 µg/g) and the Malaysian Food Regulation (100.0 µg/g). In the fish skin, the concentration of Cu and Pb were quite high. The concentration for Pb in the skin (6.77 µg/g) exceeded both the permissible limits set by FAO/WHO (1.5 µg/g) and the Malaysian Food Regulation (2.0 µg/g) while the concentration of Cu in the skin only exceeded the permissible limits set by FAO/WHO (10.0 µg/g). Among the three elements studied, Zn concentration was highest in the fish skin (45.8 µg/g). However, the Zn levels did not exceed the permissible limits of FAO/WHO and the Malaysian Food Regulation. Therefore, it can be concluded that the Tilapia caught from the waterways were not suitable for animal animal and human consumption because the concentration Pb in the fish skin was too high. Cooper was also found to be present in the skin at concentration that can pose health hazard. However, these fishes can be said to be safe to be consumed if the skin were to be removed.